Throughfall and bulk deposition of dissolved organic nitrogen to holm oak forests in the Iberian Peninsula: Flux estimation and identification of potential sources. (March 2016) - Izquieta-Rojano, S.; García-Gomez, H.; Aguillaume, L.; Santamaría, J.M.; Tang, Y.S.; Santamaría, C.; Valiño, F.; Lasheras, E.; Alonso, R.; Àvila, A.; Cape, J.N.; Elustondo, D.
Abstract: Deposition of dissolved organic nitrogen (DON) in both bulk precipitation (BD) and canopy throughfall (TF) has been measured for the first time in the western Mediterranean. The study was carried out over a year from 2012 to 2013 at four evergreen holm oak forests located in the Iberian Peninsula: two sites in the Province of Barcelona (Northeastern Spain), one in the Province of Madrid (central Spain) and the fourth in the Province of Navarra (Northern Spain). In BD the annual volume weighted mean (VWM) concentration of DON ranged from 0.25 mg l −1 in Madrid to 1.14 mg l −1 in Navarra, whereas in TF it ranged from 0.93 mg l −1 in Barcelona to 1.98 mg l −1 in Madrid. The contribution of DON to total nitrogen deposition varied from 34% to 56% in BD in Barcelona and Navarra respectively, and from 38% in Barcelona to 72% in Madrid in TF. Agricultural activities and pollutants generated in metropolitan areas were identified as potential anthropogenic sources of DON at the study sites. Moreover, canopy uptake of DON in Navarra was found in spring and autumn, showing that organic nitrogen may be a supplementary nutrient for Mediterranean forests, assuming that a portion of the nitrogen taken up is assimilated during biologically active periods. Highlights: Quantification of dissolved organic N in throughfall and bulk deposition. The highest bulk deposition rates were registered in northern Spain (12 kg ha −1 yr −1 ). Concentrations in throughfall samples were amongst the highest values ever reported. Agricultural activities and combustion processes were revealed as potential sources. Dissolved organic N may be an additional nutrient supply in Mediterranean ecosystems. Abstract : Contribution of DON to total nitrogen deposition is very important in Mediterranean forests because of anthropogenic activities.